2005
DOI: 10.1530/rep.1.00693
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic induction of spermatogenesis in the hypogonadal (hpg) mouse: role of androgens

Abstract: Testicular development is arrested in the hypogonadal (hpg) mouse due to a congenital deficiency of hypothalamic gonadotropin-releasing hormone synthesis. Previous studies have demonstrated that chronic treatment of these mice with estradiol induces testicular maturation and qualitatively normal spermatogenesis, but it is not known whether these are direct effects via estrogen receptors expressed in the testis, or indirect actions via the pituitary gland. The aim of the current studies was to determine whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…It is unlikely that Leydig cells are directly involved in the ER␣-mediated E2 induction of spermatogenesis because intratesticular steroid levels decline in E2-treated hpg males (18), and concurrent induction of circulating FSH is consistent with elevated Sertoli cell markers and limited postmeiotic germ cell development, typical of known FSH activity in androgen-deficient testes (3,44). The present findings confirm that E2 administration does not increase serum (16) or testicular (17,18) levels in hpg mice so that the E2-induced increase in seminal vesicle weight must be a direct E2 effect on seminal vesicles as reported previously (45). Therefore, the stimulatory effect of E2 for spermatogenesis in hpg mice most likely involves extratesticular ER␣ actions leading to increased circulating FSH and enhanced Sertoli cell maturation/function.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It is unlikely that Leydig cells are directly involved in the ER␣-mediated E2 induction of spermatogenesis because intratesticular steroid levels decline in E2-treated hpg males (18), and concurrent induction of circulating FSH is consistent with elevated Sertoli cell markers and limited postmeiotic germ cell development, typical of known FSH activity in androgen-deficient testes (3,44). The present findings confirm that E2 administration does not increase serum (16) or testicular (17,18) levels in hpg mice so that the E2-induced increase in seminal vesicle weight must be a direct E2 effect on seminal vesicles as reported previously (45). Therefore, the stimulatory effect of E2 for spermatogenesis in hpg mice most likely involves extratesticular ER␣ actions leading to increased circulating FSH and enhanced Sertoli cell maturation/function.…”
Section: Discussionsupporting
confidence: 74%
“…However, later studies demonstrated that comparable spermatogenesis in hpg mice is induced after similar treatment with estradiol (E2) (16). Interestingly, this E 2 effect is dependent on a functional AR (17,18) and coincides with increased circulating FSH levels. Prompted by the disparities in the available evidence on the mechanism and site of action by which E2 induces spermatogenesis in hpg mice, the present study set out to segregate the spermatogenic actions of E2 by two complementary pharmacogenetic experiments using: 1) selective estrogen receptor (ER)␣ or ER␤ agonists in gonadotropin-deficient hpg mice, and 2) pure androgen (DHT) and estrogen (E2) treatments in novel compound hpg/ER knockout lines selectively lacking ER␣ or ER␤ (hpg/␣ERKO or hpg/␤ERKO mice) on the hpg genetic background.…”
mentioning
confidence: 99%
“…Neonatal administration of weak environmental estrogens stimulates the first wave of spermatogenesis at puberty in rats (Atanassova et al 2000). Chronic treatment of the GNRH-deficient (Hpg) mice with estradiol implants can increase the size of the testis and stimulate complete spermatogenesis qualitatively (Ebling et al 2000, Baines et al 2005, Ebling et al 2006. We hypothesized that estrogenic compounds found in normal mouse food may contribute to the increase in spermatogenesis found in Gpr54 K/K and Kiss1 K/K mice as they age.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that estrogen stimulates spermatogenesis by increasing FSH secretion from the pituitary, which acts synergistically with testosterone (Baines et al 2005). E 2 -induced spermatogenesis in Hpg mice is prevented by an androgen receptor antagonist (Baines et al 2005) and requires ESR1 but not ESR2 signaling (Allan et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation